2021
DOI: 10.1038/s41598-021-85130-8
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic voice characteristics with and without wearing a facemask

Abstract: Facemasks are essential for healthcare workers but characteristics of the voice whilst wearing this personal protective equipment are not well understood. In the present study, we compared acoustic voice measures in recordings of sixteen adults producing standardised vocal tasks with and without wearing either a surgical mask or a KN95 mask. Data were analysed for mean spectral levels at 0–1 kHz and 1–8 kHz regions, an energy ratio between 0–1 and 1–8 kHz (LH1000), harmonics-to-noise ratio (HNR), smoothed ceps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
95
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(119 citation statements)
references
References 74 publications
(74 reference statements)
6
95
0
1
Order By: Relevance
“…Previous studies have found that effects of facemask use may vary according to speakers 5 . In order to investigate this, comparisons of effects of facemask use in two different populations of speakers, i.e.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Previous studies have found that effects of facemask use may vary according to speakers 5 . In order to investigate this, comparisons of effects of facemask use in two different populations of speakers, i.e.…”
Section: Discussionmentioning
confidence: 97%
“…The current investigation concerned self-perceptions of voice-related handicap associated with compulsory facemask use during COVID19 pandemic outbreak, between October 2020 and January 2021. As the impact of facemask use on phonation may differ across speakers 5 and across phonemes 7 , two populations of non-dysphonic speakers were investigated, i.e., Portuguese and Spanish, using the respective validated translations of the VHI 27,28 . All responses were obtained online, following previous recommendations on the benefits of using online surveys during outbreaks of rapidly evolving infectious diseases 31 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations